EVALUATION OF THE CRITERIA USED IN THE PERSONNEL SELECTION PROCESS WITH THE BEST-WORST METHOD (BWM) (Third Sector Social Economic Review, 2021)
The personnel selection process is a vital process for both the organization employing personnel and the recruited personnel. While choosing the right personnel provides benefits such as efficiency and productivity to the organization, it also provides benefits such as job satisfaction, commitment to the organization and life satisfaction to the recruited personnel. However, selecting the right personnel is possible by using the right selection criteria. From this point of view, in this study, it was purposed to evaluate the criteria used in the personnel selection process with the Best-Worst Method (BWM), one of the multi-criteria decision making methods. For this purpose, firstly the personnel selection process criteria used in the literature were determined, then these selection criteria were analyzed by BWM in line with expert opinions. As a result of the analysis using five criteria and 35 sub-criteria, the most important criteria are, respectively, “professional qualification criteria”, “personal characteristics criteria” and “social skills criteria”, and the most important sub-criteria are “professional knowledge and expertise”, “job/industry experience”, “professional education background”, “accuracy and honesty” and “problem solving skills” has been found.
Keywords: Personnel Selection Process; Criteria Selection; Best-Worst Method (BWM)